First Real-Time 267.8 Tb/S 2 × 70.76 Km Integrated Communication and Sensing Field Trial over Deployed Seven-Core Fiber Cable Using 130 Gbaud PCS-64QAM 1.2 Tb/S OTN Transponders - Jian Cui; Leimin Zhang; Yu Deng; Zhuo Liu; Chao Wu; Bin Hao; Ting Zhang; Yuxiao Wang; Bin Wu; Chengxing Zhang; Yong Chen; Lei Shen; et al. (Photonics)
Ultra-high-speed integrated communication and sensing (ICS) transmission techniques are highly desired for next-generation highly reliable optical transport networks (OTNs). The inherent multiple-channel advantage of uncoupled multi-core fibers (MCFs) empowers the evolution of ICS techniques. In this paper, we demonstrate an ultra-high-speed ICS OTN system utilizing 130 Gbaud probability constellation shaping 64-ary quadrature amplitude modulation (PCS-64QAM) 1.2 Tb/s OTN transponders and polarization-based sensing technique over a field-deployed seven-core MCF cable for the first time. A real-time 267.8 Tb/s 2 × 70.76 km transmission is achieved by only utilizing C-band signals thanks to the high-performance 1.2 Tb/s OTN transponders. Moreover, the ICS system can sense environmental impacts on the MCF cable such as shaking, striking, etc., in real time. The capacity of the transmission system can also be further enhanced by using signals in the L-band. Our work demonstrates the feasibility of simultaneously achieving ultra-high-speed data transmission and the real-time sensing of environmental disturbances over a field-deployed MCF cable, which we believe is a crucial milestone for next-generation ultra-high-speed highly reliable optical transmission networks.